2021
DOI: 10.1093/glycob/cwab103
|View full text |Cite
|
Sign up to set email alerts
|

Substrate complex structure, active site labeling and catalytic role of the zinc ion in cysteine glycosidase

Abstract: β-l-Arabinofuranosidase HypBA1 from Bifidobacterium longum belongs to the glycoside hydrolase family 127. At the active site of HypBA1, a cysteine residue (Cys417) coordinates with a Zn2+ atom and functions as the catalytic nucleophile for the anomer-retaining hydrolytic reaction. In this study, the role of Zn2+ ion and cysteine in catalysis as well as the substrate-bound structure were studied based on biochemical and crystallographic approaches. The enzymatic activity of HypBA1 decreased after dialysis in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The optimal temperature and pH for Bll4HypBA1 hydrolysis were estimated as 35 °C and 3.5, respectively (Figure 3). Additionally, the hydrolysis of the substrate with Bll4HypBA1 was inhibited by α/β‐ l ‐Ara f bromoacetamide [15b,c] (Figure SI‐4 and SI‐5), probably through a mechanism similar to that of Bll1HypBA1. Since Bll4HypBA1 did not show activity against any β‐ l ‐Ara f (1→2)‐ l ‐Ara f motif, Bll4HypBA1 was hypothesized to act after stepwise degradation with other bifidobacterial enzymes, such as HypAA and HypBA2.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal temperature and pH for Bll4HypBA1 hydrolysis were estimated as 35 °C and 3.5, respectively (Figure 3). Additionally, the hydrolysis of the substrate with Bll4HypBA1 was inhibited by α/β‐ l ‐Ara f bromoacetamide [15b,c] (Figure SI‐4 and SI‐5), probably through a mechanism similar to that of Bll1HypBA1. Since Bll4HypBA1 did not show activity against any β‐ l ‐Ara f (1→2)‐ l ‐Ara f motif, Bll4HypBA1 was hypothesized to act after stepwise degradation with other bifidobacterial enzymes, such as HypAA and HypBA2.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the structural characteristics of Bll3HypBA1, which contains no large structural element covering the active site. The Zn atom of Bll3HypBA1 is coordinated by Cys 3 -Glu residues, and GH127 and GH146 enzymes share this structural characteristic (Cartmell et al 2018 ; Ito et al 2014 ; Luis et al 2018 ; Maruyama et al 2022 ; McGregor et al 2021 ). In our previous studies, we elucidated the reaction mechanism of GH127 Bll1HypBA1 using synthetic inhibitors that were specifically designed for cysteine glycosidase (Ishiwata et al 2022b ; Maruyama et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…longum JCM 1217 degrades Ara f- β1,2-Ara released from Ara 3 -Hyp by GH121 β- l -arabinobiosidase (HypBA2: BLLJ_0212) (Fujita et al 2011 ). Crystallographic studies of Bll1HypBA1 have revealed that a cysteine residue serves as the catalytic nucleophile (Ishiwata et al 2022b ; Ito et al 2014 ; Maruyama et al 2022 ; McGregor et al 2021 ). In addition to GH137 and GH142 β- l -arabinofuranosidases for RG-II degradation in Bacteroides thetaiotaomicron (Ndeh et al 2017 ), GH146 was established after characterization of BT0349 as an β- l -arabinofuranosidase for arabinan-derived arabinotetraose and β1,2- l -arabinobiose (Luis et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…BtGH146 and HypBA1 were produced and purified according to the published procedures. 13,15 Intact Mass Spectrometry. rBtGH146 was diluted to 1 mg mL −1 in an SEC buffer.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…The Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acschembio.3c00558. Synthetic procedures, characterization of compounds, biochemical inhibition data, intact mass spectrometry, 1 H and 13 C NMR spectra for all newly synthesized compounds, X-ray data processing, and refinement statistics (PDF)…”
Section: * Sı Supporting Informationmentioning
confidence: 99%